#TITLE_ALTERNATIVE# - (NIM : 23409051); Pembimbing : Suprayogi, Ph.D, HARWATI
Network design is a common problem in supply chain management and logistic. It consists of decisions to determine number and location facilities, link, volume product delivered etc.Facility location problems have been studied by many previous researches. Previous models are often stressed to minimize total logistic cost. That kind of model commonly will give lowest cost of the system but it does not ensure that every facility opened will receive a well-balancing profit. This can result a new problem, where some facilities will sell product and receive profit much more than others although overall total logistic system can be minimized. This research developed mathematical model to design network for two level escelon distribution system covering number and location of facilities by considering balancing profit so that the network design resulted will give not only a minimum total logistic cost but also give a well-balancing profit for each facility. This model is then applied todetermine distribution network of LPG 3 Kg in Bantul, Yogyakarta. The application results number and location agents of LPG 3 Kg and also number and location unit served by each agent. The result of comparing between model and real system shows that the developed model has better performance than real system. It is showed by avarage difference profit of model 18,78% while the real system gives avarage difference profit 53.05%.